IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN SEJAK DINI DI SEKOLAH DASAR - Putri Oktaviana, Andini; Syifaa Nabiilah, Daffa; Agustina, Fauriza; Wahyudi, Apri (JS (JURNAL SEKOLAH), 2024)
Abstract: This research aims to investigate the impact of cultural habituation activities in schools on students' character development. Employing a qualitative approach and document study methodology, the research has revealed the significance of routine habits, spontaneity, role modeling, conditioning, school culture, and environmental health in nurturing character traits that prioritize environmental care among elementary school students. Despite commendable efforts by schools to implement character education focused on environmental care, obstacles such as students' neglect of cleanliness, lack of waste management knowledge, and the influence of their home environment have been identified. Additionally, the lack of collaboration between parents and educators has been found to hinder students' environmental consciousness. This research underscores the critical need for effective implementation of character education to promote environmental awareness and emphasizes the pivotal role of collaboration between schools and families. Keywords: Implementation, Character Education, Environmental Awareness Abstrak: Penelitian ini bertujuan untuk mengkaji bagaimana aktivitas pembiasaan budaya di sekolah mempengaruhi karakter siswa. Penelitian ini bersifat kualitatif dan menggunakan metodologi studi dokumen. Data yang diperoleh dari penelitian dapat dengan mudah dibedakan dari analisis deskriptif dari subjek penelitian. Hasil penelitian menunjukkan bahwa kebiasaan rutin, spontan, keteladanan, pengkondisian, budaya sekolah, dan kesehatan lingkungan adalah cara untuk mengajarkan karakter yang peduli dengan lingkungan di sekolah dasar. Hal-hal seperti kebiasaan buruk peserta didik yang tidak peduli dengan kebersihan mereka sendiri, kurangnya pengetahuan tentang kepedulian terhadap sampah, dan pengaruh lingkungan rumah adalah hambatan untuk mengembangkan sifat peduli lingkungan. Kurangnya kolaborasi antara orang tua dan pendidik menyebabkan siswa kurang peduli terhadap lingkungan. Meskipun ada beberapa hambatan, sekolah telah berusaha keras untuk menerapkan pendidikan karakter peduli lingkungan. Kata kunci : Implementasi, Pendidikan Karakter, Peduli Lingkungan